MODEL EMPIRIS MINAT ENTREPRENEURSHIP DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Rahmawaty, Anita (EQUILIBRIUM, 2019)
This research aims to analyze the model of the intention entrepreneurship based on Theory of Planned Behavior (TPB). This research is a survey research by using a quantitative approach. The research data are obtained from 225 respondents by using random sampling technique. The research model testing technique uses the path analysis approach. The results showed that the emotional intelligence positively and significantly effects on entrepreneurial attitude, subjective norms, self-efficacy and intention entrepreneurship. Nevertheless, in this research, it is found also that the  entrepreneurial attitude is  not  related  to  intention entrepreneurship. Thus, the research findings suggest that emotional intelligence is the important variable that affect on self-efficacy and intention entrepreneurship.